Eurodynamic Sdn. Bhd. / Sharina Mohd Nasir, Atfina Naemah Omar and Nursalwa Samsuri. - Mohd Nasir, Sharina; Omar, Atfina Naemah; Samsuri, Nursalwa
EURODYNAMIC Sdn. Bhd. (ESB Flying Club) or also known as ESB is owned by one of the ambitious and successful Malay-entrepreneur, Mr. Raffick bin Mohd Noh. Its headquarters is located at SSI9 Subang Jaya while its hangar is located at Sultan Abdul Aziz Shah Airport, Subang, Selangor. Nature of his business is providing a flying lesson class for them who want to have a pilot license and interested to become a pilot. This flying class lesson is divided into two sections which is section A: Theory class (ground school); and section B: Practical class (flight school). For theory class, it being handled in the classroom completes with the facilities for student comfortably in having their lecture and tutorial; while for practical class, it being handled in two phase: first phase, using flying simulator software and second phase, using aircraft. ESB also providing a renting aircraft service for anyone who had a unique hobby spending their leisure time on air and for this purpose, they have to register as the member of this flying club. ESB is using two-seater light aircraft for both flying class and renting service on safety and economic reason. According to Mr. Raffick, he has selected this business because it is a very competitive and profitable business, besides it has a bright prospect in the present and in the future. As a matter of facts, nowadays we have been witnessing the potential of ASEAN as the main air-entrance to the continent of Asia and in this case, Malaysia is being the spot light because Kuala Lumpur International Airport (KLIA) has played the role as the main entrance for ASEAN to having the outsiders, especially foreigners. Rate of the foreigners that come to the ASEAN, especially Malaysia is increasing year by year and it gives the good effect to the economic development. Therefore, tourism is one of the best assets and the best way to bring the continent of Asia especially Malaysia as well as ASEAN to the world wide which is from this, profits for the country development could be gain. So, to make sure that Malaysia and ASEAN is ready to face the world through the tourism sector, more pilots are needed to fly the plane; and to fulfill the job vacancy, ESB will be taking the precious opportunity to be the best starting point for the pilots to get their training and license with no doubt.